MODELING OF SEDIMENT TRANSPORT IN THE DRAINAGE CHANNELS WAY OF REHABILITATION- CASE OF BOUTHEA -NORTH EST PLAIN OF ALGERIA - & et al., Foued (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The Drainage of agricultural land has become a top priority in agriculture, at the level of developing countries it is directly related to human life and economic development of the state. The objective of this article is to quantify and estimate morphological evolution in the medium term. the morphological evolution of the canals under the influence of sedimentary transport processes. The study area consists of agricultural land located in the plain of Bouteldja, in the north-east of Algeria. This zone was developed in 2006 as part of a hydro-agricultural project through the creation of networks of open-air drainage channels, but until now submerged with adjacent farmland. The causes may be: i) the lack of cleaning maintenance since completion, ii) the existence of drained males. To model the sediment transport process in the drainage canals, we used the empirical formulas and models of the HEC-RAS software. These models were calibrated to actual data obtained during the observation period from 2017 to 2018 for the various rain events, the model results give good criteria.